Image-schematic Metaphors of LIFE in Latin Mourning Poetry of the Late 16th Century in the Grand Duchy of Lithuania - Seredžiūtė, Viktorija (Respectus Philologicus, 2017)
This article analyses the Latin mourning poetry of the late 16th century in the Grand Duchy of Lithuania (GDL). Funeral verses chosen for analysis are written by the students of Vilnius Academy and Renaissance poet Petrus Royzius. This article aims at revealing the specificity of image-schematic metaphors LIFE IS A JOURNEY, LIFE IS A THREAD and LIFE IS A SCALE of the mourning poetry of the late 16th century in the GDL. George Lakoff suggests source-path-goal scheme, which refers to moving from point A (source) to point B (goal). The study reveals that schema of a path metaphorically is connected with life in this world from birth until death, and schema of scale is connected with afterlife (heaven, Olympus is direction UP; underworld, Tartarus, Hades is direction DOWN). Conceptual metaphors LIFE IS A JOURNEY and LIFE IS A THREAD reveals that people realised its impermanence and fragility. LIFE IS A SCALE is related to Christian conception of afterlife: clean-lived people come to God in Heaven and unrighteous come to Tartarus.